KOMPARASI KOMPETENSI PEDAGOGIK GURU AKUNTANSI YANG SUDAH DAN BELUM MENGIKUTI SERTIFIKASI - Wilis Puspita Dewi, (Pendidikan Ekonomi, 2011)
The study was set out to compare analytically the pedagogical competence of the certified teachers and that of those are not certified at SMKN Negeri 2 Kediri. The study was comparative research with accounting teachers as the subjects of the study. The data were collected by means of interview protocols, observation sheets, and self-reported questionnaires. The data obtained form interview and observation were then analyzed descriptively, while those of questionnaires were analyzed using independent t-test. The result of the study shows that the pedagogical competence of the accounting teachers who have been certified is better than those who have not.